The Influence of Financing Risk on Mudharabah Financing in Islamic Commercial Banks - Endra Herdiansyah; Fadhila Nurul Azqia; Annisa Adha Minaryanti; Budi Septiawan (Journal of Creative Power and Ambition (JCPA), 2026)
The Influence of Financing Risk on Mudharabah Financing in Islamic Commercial Banks